Application of VR/AR technology for visualisation of radiation tolerance of VLSI. (9th April 2020) - Shakhnov, V.A.; Kazakov, V.V.; Glushko, A.A.; Rezchikova, E.V.; Sorokin, B.S.; Tsivinskaya, T.A.; Verstov, V.A.; Zinchenko, L.A.
A correct perception of a link between the heavily charged particles parameters and radiation tolerance of very large integrated circuits is one of the main problems in design of electronic equipment for space applications. In the paper, methods of augmented/virtual reality applications for research of radiation damage on very large integrated circuits (VLSI) are introduced. A transfer function design for correct visual representation is discussed. In the paper, we assume transfer function transforms the number of particles damaging a chip to a colour from green to red. The red colour means that the chip has been damaged. The green image means the initial conditions. We discuss features of augmented reality realisation with minimal hardware requirements. Our tool can help engineers to compare alternative design solutions.